A Critical View on PLM/ALM Convergence in Practice and Research. (2016) - Deuter, Andreas; Rizzo, Stefano
Abstract: The Internet of Things (IoT) is the main driver for industrial smart products produced by an increasing number of manufacturers. The overall functionality of smart products is a combination of mechanical, electrical/electronic functions (hardware functions) and software functions. For hardware and software there are different lifecycle models: Product lifecycle management (PLM) focuses on hardware, application lifecycle management (ALM) focuses on software. Smart products force manufacturers to converge both lifecycle models step by step. Although seemingly important, the research community leaves this innovative area mostly up to the PLM tool vendors and the ALM tool vendors, resulting in them driving the convergence. This paper points out the mismatch between industry and academia regarding the PLM/ALM convergence. We encourage academia to increase research activities and we propose potential research topics.